PENERAPAN METODE PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ASMAUL HUSNA DI KELAS IV SD NEGERI 1 SLOROK - Jannah, Alvina Rohmatul; Ali, Nur; Yasin, Ahmad Fatah (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
Based on the author's observations at SD Negeri 1 Slorok, it shows that student learning outcomes are still lacking. This has the following symptoms: (a) Students do not pay attention to the teacher's explanation of the learning material. (b) During learning, there are students playing. (c) Students are not serious about learning. (d) Students feel bored, this can be seen by several students going in and out of the classroom. (e) Students are indifferent when the teacher explains the learning material. From the several symptoms mentioned above, it shows that students' interest in studying Asmaul Husna material is still lacking so that student learning outcomes are also low. This is possible due to students' lack of understanding. This research is based on the problem: How do learning outcomes improve using the Problem Based Learning Model in PAI learning Asmaul Husna material in class IV of SD Negeri 1 Slorok? Meanwhile, the aim of this research is to determine the improvement in learning outcomes using the Problem Based Learning Model in PAI learning Asmaul Husna material in class IV of SD Negeri 1 Slorok. This research used two rounds of classroom action research. Each round consists of four stages, namely: Planning, Action, observation and reflection. The target of this research is class IV students for the 2022-2023 academic year. The data obtained were in the form of research post test results, observation sheets of teaching and learning activities. From the analysis results, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (70%), cycle II (90%). The conclusion from this research is that the application of the Problem Based Learning (PBL) Learning Model is able to improve students' Islamic Religious Education Learning Outcomes on Asmaul Husna material. The use of snakes and ladders media and maching cards has a very significant impact in helping to implement the Problem Based Learning Model. Abstrak Berdasarkan pengamatan penulis di SD Negeri 1 Slorok yang menunjukan hasil belajar siswa masih kurang. Hal ini terdapat gejala-gejala sebagai berikut: (a) Siswa tidak memperhatikan penjelasan guru tentang materi pembelajaran. (b) Pada saat pembelajaran berlangsung ada siswa yang bermain. (c) Siswa tidak bersungguh-sungguh dalam mengikuti pembelajaran.(d) Siswa merasa bosan, hal ini terlihat ada beberapa siswa yang keluar masuk ruangan kelas. (e) Siswa acuh saja ketika guru menjelaskan materi pembelajaran. Dari beberapa gejala yang tersebut diatas menunjukan bahwa minat siswa untuk mempelajari materi Asmaul Husna masih kurang sehingga hasil belajar siswa juga rendah. Hal ini dimungkinkan karena ketidakpahaman siswa. Penelitian ini berdasarkan permasalahan: Bagaimana peningkatan hasil belajar menggunakan Model Problem Based Learning pada pembelajaran PAI materi asmaul husna di kelas IV SD Negeri 1 Slorok?. Sedangkan tujuan penelitian ini untuk mengetahui peningkatan hasil belajar menggunakan Model Problem Based Learning pada pembelajaran PAI materi asmaul husna di kelas IV SD Negeri 1 Slorok. Penelitian ini menggunakan penelitian tindakan kelas sebanyak dua putaran. Setiap putaran terdiri dari empat tahap yaitu : Perencanaan, Tindakan, observasi dan refleksi. Sasaran penelitian ini adalah siswa kelas IV Tahun pelajaran 2022-2023. Data yang diperoleh berupa hasil post test penelitian, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus II yaitu, siklus I (70%), siklus II (90%). Simpulan dari penelitian ini penerapan Model Pembelajaran Problem Based Learning (PBL) mampu meningkatkan Hasil Belajar Pendidikan Agama Islam siswa pada materi asmaul husna. Penggunaaan media ular tangga serta maching card mempunyai dampak yang sangat signifikan dalam membantu terlaksananya Model Pembelajaran Problem Based Learning.